2005
DOI: 10.1111/j.1742-1241.2005.00525.x
|View full text |Cite
|
Sign up to set email alerts
|

Are we good at thromboembolic disease prophylaxis? - an audit of the use of risk assessment forms in emergency medical admissions

Abstract: Venous thromboembolism (VTE) is a major cause of morbidity and mortality in hospitalised patients. Thromboprophylaxis is an effective strategy for VTE prevention in high-risk patients. An initial audit in our district general hospital trust showed poor adherence to the thromboembolic risk factors consensus group recommendations and so a risk assessment form (RAF) was devised. We present repeated audits to assess the RAF uptake and its effects on VTE thromboprophylaxis. We also present data analysing perception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
3

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
0
6
0
3
Order By: Relevance
“…Despite the importance of VTE prophylaxis, a blanket prescribing approach is not appropriate as low molecular weight heparins (LMWH) are associated with increased incidence of bleeding in certain patient groups. It is therefore imperative that all new patients undergo a risk assessment to determine suitability for VTE prophylaxis and have LMWH prescribed as appropriate (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the importance of VTE prophylaxis, a blanket prescribing approach is not appropriate as low molecular weight heparins (LMWH) are associated with increased incidence of bleeding in certain patient groups. It is therefore imperative that all new patients undergo a risk assessment to determine suitability for VTE prophylaxis and have LMWH prescribed as appropriate (6).…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the demanding nature of the admissions unit, the lack of stability of a fixed medical team and additional human factors, patients can often have their VTE risk assessment and subsequent prophylaxis missed, putting them at risk. A previous study at this trust concluded that despite awareness of the importance of VTE prophylaxis, a common reason for non‐compliance was forgetfulness (6).…”
Section: Introductionmentioning
confidence: 99%
“…Las guías de recomendación para la profilaxis de la ETEV en diferentes especialidades se han publicado y distribuido desde hace décadas, especialmente en la especialidad de C.O.T. Existen numerosas publicaciones donde se evalúa la cumplimentación de las guías según las diferentes especialidades, así como dentro de las mismas sobre patologías concretas 7,8,9,21,56,129,244,269,272,286,292,316,329,334,338,362,393 . En primer lugar cabría destacar que, aunque el desarrollo de una guía clínica basada en la evidencia esté basada sobre un entorno o país concreto, puede que la misma no se adapte bien a lugares ajenos o diferentes al mismo, como se reflejó en el trabajo de Sakon y cols.…”
Section: Discussionunclassified
“…Diferentes publicaciones evalúan las guías clínicas en función de las especialidades médicas 7,56,220,292,316,362 , de todas las especialidades dentro del ámbito hospitalario 21,286,334 y de C.O.T 8,9,129,244,269,338,393 . Dentro de la propia especialidad de C.O.T., existen guías específicas de cirugías concretas, para su mejor manejo, como son la cirugía mayor ambulatoria en C.O.T 24 , cirugía artroscópica 380 , PTC 142, 346 y PTR 324,347 .…”
Section: Discussionunclassified
See 1 more Smart Citation